2008
DOI: 10.1121/1.2871597
|View full text |Cite
|
Sign up to set email alerts
|

Localization of multiple acoustic sources with small arrays using a coherence test

Abstract: Direction finding of more sources than sensors is appealing in situations with small sensor arrays. Potential applications include surveillance, teleconferencing, and auditory scene analysis for hearing aids. A new technique for time-frequency-sparse sources, such as speech and vehicle sounds, uses a coherence test to identify low-rank time-frequency bins. These low-rank bins are processed in one of two ways: (1) narrowband spatial spectrum estimation at each bin followed by summation of directional spectra ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 18 publications
1
110
0
1
Order By: Relevance
“…It does this by projecting the received signals in a DOA subspace based on their eigenvectors, similar to principal component analysis. It was applied in [14] with good results, although it has been observed that its performance decreases considerably in the presence of reverberation [38] (pp. 169).…”
Section: Challenges In Estimating Multiple Doas In a Mobile Robotic Pmentioning
confidence: 99%
“…It does this by projecting the received signals in a DOA subspace based on their eigenvectors, similar to principal component analysis. It was applied in [14] with good results, although it has been observed that its performance decreases considerably in the presence of reverberation [38] (pp. 169).…”
Section: Challenges In Estimating Multiple Doas In a Mobile Robotic Pmentioning
confidence: 99%
“…It does this by projecting the received signals in a DOA subspace, based on their eigenvectors, similar to Principal Component Analysis. It was applied in [9] with good results, although it has been observed that its performance decreases considerably in the presence of reverberation [21] (pp. 169).…”
Section: On Source Direction Estimationmentioning
confidence: 99%
“…However, coherent reflections are not independent and so the effective rank is less than the total number of sources and reflections. To improve the identification of TF-regions whose effective rank is one, the coherence test proposed in [7] averages the correlation matrix over time. The Direct-Path Dominance (DPD) test [8] leads to further improvement using frequency smoothing by also averaging the correlation matrix over frequency thus decorrelating coherent reflections.…”
mentioning
confidence: 99%